OUTCOMES OF GRADE IV-V KIDNEY TRAUMA AT VIET DUC FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the treatment outcomes of severe kidney trauma (grade IV-V).Subjects and methods: A retrospective study of 117 patients with grade IV-V kidney trauma who were diagnosed, treated, monitored, and underwent either vascular intervention or surgery from January 2020 to March 2024. Collected parameters included age, gender, cause of kidney trauma, time from injury to hospital admission, patient condition at admission, classification of kidney trauma (isolated kidney trauma, combined trauma, trauma in pathological kidneys), biochemical and hematological tests, ultrasound findings, and classification of kidney trauma severity on CT imaging according to the 2018 AAST grading system. Clinical diagnostic forms of kidney trauma included pseudoaneurysm, arteriovenous fistula, infected or abscessed retroperitoneal hematoma-urinary extravasation. Short-term (postoperative) and long-term (3 months post-treatment) outcomes were evaluated.Results: The mean age of the study group was 33.6 ± 16.6 years, with the most commonly affected age group being 50-59 years (26.5%). The male-to-female ratio was 4.6/1. Blunt abdominal trauma combined with kidney trauma was the most common cause (42.7%), followed by blunt chest trauma (23.1%). A total of 31 patients (26.5%) had associated injuries involving 2 organs. Angioembolization and interventional methods accounted for a high percentage (53.8%), with isolated embolization being the most common approach (37.6%), followed by embolization combined with JJ stent and laparoscoy remove hematoma-urinary (6.8%). Among the 117 patients with grade IV and V kidney trauma, the highest proportion of patients had good treatment outcomes at discharge (40.1%), while 36.8% had moderate outcomes, and 23.1% had fair outcomes. Among 87 patients who returned for follow-up, 2 cases (2.3%) developed kidney atrophy as a late complication, but no other long-term complications such as hypertension or renal failure were recorded.Conclusion: The rate of kidney trauma cases managed with conservative treatment has been increasing, even for Grade IV and, in some cases, Grade V injuries.
Keywords: Kidney trauma, renal angioembolization.